(untitled) (Research, Society and Development, 2021)
This paper aims to analyze the influence (negative or positive) of macro and microeconomic variables on Petrobras stock price for 12 years, between 2009 and 2020. The methods employed were: i) Pearson’s correlation and; ii) Ordinary Least Squares (OLS). The literature review was helpful to understand the qualitative aspects. The main results obtained from both methodologies pointed out that Petrobras’ Stock prices were affected by Brent oil price, Ibovespa index, and Production level. These variables were statistically significant in the OLS to explain the fluctuations in the PETR4 share price. Finally, it is worth mentioning that political factors, governance failures (and acts of corruption), Fuel Price Policy, the Political Scenario, and the company’s Financial Indicators can also considerably influence the price of PETR4.